TINJAUAN STATUS GIZI SISWA PADA SMPS WAHIDIN BANGKO KECAMATAN BANGKO - Diantius, Elfri; Wijayanti, Ni Putu Nita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
ABSTRACT, The background of the problem in this study originated from the observation while in SMPS Wahidin Bangko, researchers found that many students were not excited when the learning because it is suspected of being owned nutritional status of students. Therefore, the purpose of this study was to determine how the nutritional status of students SMPS Wahidin Bangko. This type of research is descriptive quantitative research. This study describes clearly how where the nutritional status of students SMPS Wahidin Bangko. In accordance with the findings of a problem at a school in the district of Bangko on nutritional status of students. The research data was obtained from measurements of height and weight of students. The sample in this study was the students of class VII numbering 39 people (total sampling). Based on the research results can be concluded as follows: It was found that nutritional status is processed through BB / U of overall VII.I grade students who are 39 students were having Good Nutrition as many as 20 people with a percentage of 51.82%, the students who has satatus Nutrition Medium as many as 13 with the percentage 33.33%, students have much less Nutrient satatus 6 with a percentage of 15.38%, while students malnourished nothing. The average score of the assessment of the nutritional staus seventh grade students is 10 with a percentage of 25.64%. Therefore, based on the average score of the overall nutritional status of students SMPS Wahidin District of Bangko Bangko categorized Less Good.Keywords : Observation, Nutrition Status